2019
DOI: 10.1051/e3sconf/201910702004
|View full text |Cite
|
Sign up to set email alerts
|

Induced electromagnetic field on underground metal pipelines running parallel to nearby high voltage AC power lines

Abstract: High voltage AC (HVAC) power lines can induce significant amount of voltages on underground gas/oil metal pipelines in areas where they share similar Right of Way (RoW), the situation becoming serious particularly in case of fault conditions. Electromagnetic field generated by the HVAC power lines on these pipelines, generate unwanted voltages which present threats to the pipeline and its associated protective equipment such as cathodic systems. The aim of this research is to compute induced voltage on pipelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It was found that when the pipeline crosses the line from a small angle to a large angle, the interference suffered by the pipeline can be reduced. Dushimimana et al [ 21 ] investigated the influence of high‐voltage AC transmission lines on AC interference voltage and induced electromagnetic field of adjacent pipelines under the steady operation and fault conditions of AC transmission lines with different influence parameters such as parallel length, parallel interval, and load currents. It was found that the induced voltage increases with the increase of load current, and it is inversely proportional to the cross angle, the smaller the angle the higher the induced voltage.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when the pipeline crosses the line from a small angle to a large angle, the interference suffered by the pipeline can be reduced. Dushimimana et al [ 21 ] investigated the influence of high‐voltage AC transmission lines on AC interference voltage and induced electromagnetic field of adjacent pipelines under the steady operation and fault conditions of AC transmission lines with different influence parameters such as parallel length, parallel interval, and load currents. It was found that the induced voltage increases with the increase of load current, and it is inversely proportional to the cross angle, the smaller the angle the higher the induced voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high cost of right-of-ways, it is in fact unavoidable that the pipelines share the same corridor with high-voltage AC (HVAC) power lines [4][5][6]. It is then likely that electromagnetic interference may occur, where the source is constituted by the HVAC power line and the victim by the metallic buried pipeline [7][8][9]. In general, this electromagnetic interference consists of inductive, capacitive and conductive contributions [10] which can be studied and assessed with three different coupling mechanisms.…”
Section: Introductionmentioning
confidence: 99%